Osteological description of Zingel balcanicus (Teleostei: Percidae) - Julijana Arsovska1, Milica Ristovska1, Vasil Kostov, Dana Prelic & Valentina Slavevska-Stamenkovic (Springer, Institute of Zoology, Slovak Academy of Sciences, 2014)
Recent field studies have shown that the survival of Zingel balcanicus (Karaman, 1937) was enabled in an isolated area along the Treska River. The presence of two opercular spines in Z. balcanicus, compared to only one in Zingel streber, has attracted our interest for investigating more details about osteological characters of Z. balcanicus in order to provide more useful anatomical data that could be of osteo-taxonomic value. A complete osteological description of Z. balcanicus is presented with some comparative aspects discussed. Zingel balcanicus shares a large number of osteological characteristics with other members of Zingel. However, the articular processes of the premaxillary bone, teeth in the palatine bone, opercular spination and number of precaudal centra were emphasised as stable osteo-taxonomic characters. On the other hand, the architecture of the hyomandibula, spine-like extensions of infraorbital bones, gill rakers, and independent cartilage plates and presence of “Spreitzer vertebra” were noticed as peculiar characteristics that never have been described for the genus Zingel.
Keywords: fish; osteology; Percidae; Zingel